Merged Svalbard digital terrain model - Itkin, Mikhail; Moholdt, Geir; Wesselink, Dieuwertje; Aas, Harald Faste (Norwegian Polar Institute, 2019)
A 20m DEM mosaic in UTM33 projection with newest NPI products and filtered ASTER GDEM elsewhere (South Spitsbergen and NW tip of Spitsbergen). Time span is mostly 2008-2012 for elevations, and the extent has been cut to the coastline of 2015.